Potential application of rain garden towards sustainable urban ecosystem and environment for streetscapes - Salim, Farha; Bohari, Amrina Rosyada; Abu Bakar, Aniza (2013)
Increased storm water runoff is a major concern in urban areas and it is mostly from the impervious surfaces. Therefore, the study of this research is on the potential application of rain garden in sustaining urban streetscapes as an innovative means for stormwater management to overcome the urban stormwater issues. The potential implementation of rain garden systems, types, and elements are further studied to discover the potential fitness in streetscapes particularly on street plantings. Native plants selection is one of a crucial part in enhancing the rain garden implementation. Then the most potential and ideal rain garden systems are recognized according to the level of issues and physical condition on the sites. The suggested implementation simply promotes vibrant living in urban area and harmonizes the relationship between green spaces and buildings spaces. Pedestrian walkway is one of the streetscapes elements identified that in need the rain garden system. Information was collected through the previous findings by some former researchers and it was supported by some local guidelines. A case study was conducted and the data collected were then compared to each other and with the existing condition of the sites that have been observed through field observation method. For median road and pedestrian walkways, open rain gardens would be the most suitable way to be applied where it holds a layer of pervious soil, which combines water restoration with plant life. It is recommended that the best materials that can be used for hard surface is interlocking bricks that can infiltrate the water effectively, and helped by the existence of vegetated land. Keywords: Rain garden, rain garden potential, streetscapes, stormwater runoff, storm water management